Inventor networks in renewable energies: The influence of the policy mix in Germany - Uwe Cantner; Holger Graf; Johannes Herrmann; Martin Kalthaus (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2014)
Technological change and gains in efficiency of renewable power generation technologies are to a large extent driven by governmental support. Various policies that can broadly be categorized as technology push, demand pull or systemic constitute a policy mix for renewable energies. Our goal is to gain insights on the influence of this policy mix on the intensity and organization of inventive activities within the technological innovation systems for wind power and photovoltaic in Germany since the 1980s. We examine the effect of different instruments on the size and structure of co-inventor networks based on patent data. Our results indicate notable differences between the technologies: The network size for wind power is driven by technology push and systemic instruments, while in photovoltaic demand pull is decisive for network growth. The instruments complement each other and form a consistent policy mix. The structure of the networks is driven by demand pull for both technologies. Systemic instruments increase interaction especially in the wind power network and are complementary to demand pull in fostering collaboration.
Keywords: Q42; Q55; L14; O38; 330; demand pull; inventor network; policy mix; renewable energy; systemic instrument; technology push